2021
DOI: 10.3390/biom11050756
|View full text |Cite
|
Sign up to set email alerts
|

Sweet Modifications Modulate Plant Development

Abstract: Plant development represents a continuous process in which the plant undergoes morphological, (epi)genetic and metabolic changes. Starting from pollination, seed maturation and germination, the plant continues to grow and develops specialized organs to survive, thrive and generate offspring. The development of plants and the interplay with its environment are highly linked to glycosylation of proteins and lipids as well as metabolism and signaling of sugars. Although the involvement of these protein modificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 470 publications
(796 reference statements)
0
18
0
Order By: Relevance
“…The growth and development of plants as well as the interplay with its environment are closely linked to protein glycosylation. In contrast to traditional N-/O- glycosylation, O-GlcNAcylation has been relatively less appreciated. However, emerging evidence suggests that O-GlcNAcylation plays critical roles in plant physiology and pathology.…”
Section: Species Distribution Of O-glcnacylationmentioning
confidence: 99%
“…The growth and development of plants as well as the interplay with its environment are closely linked to protein glycosylation. In contrast to traditional N-/O- glycosylation, O-GlcNAcylation has been relatively less appreciated. However, emerging evidence suggests that O-GlcNAcylation plays critical roles in plant physiology and pathology.…”
Section: Species Distribution Of O-glcnacylationmentioning
confidence: 99%
“…Though jacalin-related lectins can occur as single lectin domain proteins, the subgroup of mannose-binding jacalin-related lectins also comprises proteins containing multiple (2)(3)(4)(5)(6) in tandem arrayed lectin domain repeats [104][105][106]. In addition, several grass species (including wheat (Triticum aestivum L.), rice, maize (Zea mays L.) and bamboo (Phyllostachys edulis (Carrière) J.Houz.)…”
Section: Stress-inducible Jacalin-related Lectinsmentioning
confidence: 99%
“…Yet, most plant carbohydrates are part of more complex structures, including, e.g. storage polysaccharides (starch and fructans), cell wall components, glycoproteins and glycolipids [ [3,4] and references cited therein]. Although in the early days of lectinology, research mainly focused on lectin interactions with monosaccharides and oligosaccharides, today the pool of known carbohydrate structures that bind lectins is extended and diverse, contributing to our understanding of the roles for lectins in plants.…”
mentioning
confidence: 99%
“…The soil’s health status promotes its agricultural sustainability ( Odelade & Babalola, 2019 ). Various studies have demonstrated the effects of microorganisms on tomatoes regarding their size and development, proper seed multiplication, nutrition, disease resistance, and seedling development ( De Coninck et al, 2021 ; Patil & Fauquet, 2021 ). In addition, the soil factors affecting plant growth are as follows; dissolved oxygen concentration, nutrients, phytopathogens and parasites, water, and weed seed pools ( Patil & Fauquet, 2021 ).…”
Section: Introductionmentioning
confidence: 99%